Allulose crystallization composition
Patent Information
- Application Number
- JP2022099412
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-28
- Filing Date
- 2022-06-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2039-02-07
Smart Images

Figure 0007936679000009 
Figure 0007936679000010 
Figure 0007936679000011
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing crystalline functional sweeteners, and more particularly to a method for producing allulose crystals that increase crystal yield and particle size by controlling the content of impurities converted from allulose during the process of producing crystalline functional sweeteners, such as allulose crystals. The present invention also relates to an allulose crystallization composition in which the content of allulose converter (Impurity-S) is adjusted to a specific concentration range, resulting in uniform particle size and reduced losses in the recovery process, thereby improving crystal yield. [Background technology]
[0002] While general sugars, represented by sucrose and starch, form the largest market worldwide at approximately 65 trillion yen, the growing global consumer demand for health-conscious, functional, and premium products is driving the growth of the markets for sugar alcohols such as xylitol, oligosaccharides such as fructooligosaccharides, functional sugars such as crystalline fructose, and functional sweeteners such as sucralose and aspartame.
[0003] Sweeteners are a general term for seasonings and food additives that provide a sweet taste. Among the many sweeteners, sugar, glucose, and fructose are the most widely distributed as natural components in food and are also the most widely used in the production of processed foods. However, with the negative aspects of sugar, such as causing tooth decay, obesity, and diabetes, functional alternative sweeteners that can be used as a substitute for sugar are attracting attention worldwide.
[0004] Recently, allulose has been attracting attention as a functional sweetener that can replace sugar or fructose. Allulose is produced by chemical or biological methods, but because the allulose content in the product is low, purification and concentration processes are necessary. However, there are limitations to the application of concentrated syrup, so there is a high demand for crystalline powder, but allulose is difficult to crystallize due to its low crystallinity. Furthermore, even when allulose is produced by biological methods using allulose convertase or bacterial strains that produce the enzyme, the purity of D-allulose must be increased due to the low conversion rate before crystallization. Therefore, when aiming for the industrial use of D-allulose, unresolved issues remain regarding the purification process, purification yield, and crystallization yield.
[0005] Therefore, there is a pressing need for a method to produce allulose crystals that increase crystal yield and particle size by minimizing the amount of impurities contained in the allulose solution for crystallization or the generation of impurities during the allulose manufacturing process, and by controlling the amount of impurities converted from allulose. [Overview of the project] [Problems that the invention aims to solve]
[0006] The present invention relates to a method for producing allulose crystals that increases crystal yield and particle size by controlling the amount of impurities contained in a solution for producing crystals or the generation of impurities.
[0007] Furthermore, the present invention provides a method for producing allulose crystals that have a uniform particle size by appropriately adjusting the growth of crystal particles, thereby reducing losses in the recovery process, improving crystal yield, and increasing the productivity of the allulose crystallization process.
[0008] Furthermore, the present invention provides an allulose crystallization composition in which the content of allulose converter (Impurity-S) is adjusted to a specific concentration range, which has a uniform particle size and can reduce losses in the recovery process, thereby improving the crystal yield. [Means for solving the problem]
[0009] The present invention relates to an allulose crystallization composition having a uniform particle size, which reduces losses in the recovery process and thus improves crystal yield, and to a method for producing allulose crystals using the same, wherein the content of an allulose converter (Impurity-S) is adjusted to a specific concentration range. Furthermore, the present invention relates to a method for producing allulose crystals that increases crystal yield and particle size by controlling the impurity content or generation of impurities contained in the solution for producing crystals.
[0010] Because allulose is less stable at lower pH and higher temperatures (Figures 2 and 3), its content changes during the actual production process, particularly during the concentration stage. This problem reduces the purity of high-purity allulose and significantly affects the crystallization stage. In fact, the decrease in allulose content during this process increases the content of additionally generated allulose converters (impurities), and this invention has confirmed that this component has a significant impact on allulose crystallization. Among the various allulose converters, the presence of a component called Impurity-S was found to act as an inhibitor on the growth of allulose crystal particles, and it was discovered that this significantly affects the particle size and crystal yield of the crystal particles.
[0011] Accordingly, in performing the allose crystallization step, the present invention adjusts the content of impurities (Impurity-S) to a specific content or less, for example, 2% by weight or less, at the stage before and after concentration after the high-purity separation step, whereby it is possible to prevent the size of allose particles from becoming smaller, and to produce allose having a uniform particle size by appropriately adjusting the growth of crystal particles. In addition, by growing the particles to a uniform size, it is possible to reduce loss in the recovery step, improve the crystal yield, and enhance productivity.
[0012] The allose syrup, which is the raw material used in the allose crystallization step, may contain various allose conversion products that are impurities other than allose generated in the process of producing allose, or the allose conversion products may be generated in the allose crystallization step. By adjusting (controlling) the content of a specific conversion product (hereinafter referred to as Impurity-S) among the conversion products to a specific content or less, for example, 2% by weight or less, the shape, structure and size of allose crystal particles, crystal purity, crystal formation rate, and crystal yield can be improved. The Impurity-S prevents the allose crystal particles from growing, and thus acts as an inhibitor that lowers the crystal yield. The present invention provides a method capable of increasing the allose crystal grain size and improving the yield by controlling the allose production process under conditions where no allose conversion products are generated.
[0013] The allose convert product (Impurity-S) may be a substance having a mass-to-charge ratio measured by an LC / MS analysis method in the range of 10 to 600 m / z, 10 to 550 m / z, 10 to 500 m / z, 10 to 450 m / z, 10 to 400 m / z, 20 to 600 m / z, 20 to 550 m / z, 20 to 500 m / z, 20 to 450 m / z, 20 to 400 m / z, 30 to 600 m / z, 30 to 550 m / z, 30 to 500 m / z, 30 to 450 m / z, 30 to 400 m / z, 40 to 600 m / z, 40 to 550 m / z, 40 to 500 m / z, 40 to 450 m / z, 40 to 400 m / z, 50 to 600 m / z, 50 to 550 m / z, 50 to 500 m / z, 50 to 450 m / z, or 50 to 400 m / z, or may be a substance having a maximum peak measured at an elution time of 31±2 minutes when analyzed by an HPLC analysis method. The LC / MS analysis method is for analyzing a substance obtained by separating a substance having a maximum peak measured at an elution time in the range of 31±2 minutes as analyzed by the HPLC analysis method.
[0014] Furthermore, the allulose converter (Impurity-S) may be an allulose modified product, an allulose modified polymer, or an intermediate substance produced and converted during the decomposition process of allulose, and the molecular weight of the allulose converter (Impurity-S) has a lower limit of 0.2 times, 0.3 times, 0.4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1 time, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, Or more than twice, the upper limit may be 10 times or less, 9 times or less, 8 times or less, 7 times or less, 6 times or less, 5 times or less, 4 times or less, 3 times or less, 2 times or less, less than 1.5 times, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1 time or less, 0.9 times or less, 0.8 times or less, 0.7 times or less, 0.6 times or less, 0.5 times or less, 0.4 times or less, 0.3 times or less, or 0.2 times or less, and the molecular weight of the allulose convertible may have a molecular weight within the numerical range set by the combination of the lower limit and the upper limit, for example the allulose convertible The molecular weight of allulose is 0.4 to 10 times, 0.5 to 10 times, 0.53 to 10 times, 0.4 to 9 times, 0.5 to 9 times, 0.53 to 9 times, 0.4 to 8 times, 0.53 to 8 times, 0.4 to 7 times, 0.4 to 6 times, 0.4 to 5 times, 0.4 to 4 times, 0.4 to 3 times, 0.4 to 2 times, 0.4 to less than 1.5 times, 0.4 to 1.5 times or less, 0.4 to 1.4 times, 0.4 to 1.3 times, 0.4 to 1.2 times, 0.4 to 1.1 times, 0. 4x or more to 1x, 0.4x or more to 0.9x, 0.4x or more to 0.8x, 0.4x or more to 0.7x, 0.4x or more to 0.6x, 0.4x or more to 0.5x, 0.5x or more to 7x, 0.53x or more to 7x, 0.4x or more to 6x, 0.5x or more to 6x, 0.5x or more to 5x, 0.5x or more to 4x, 0.5x or more to 3x, 0.5x or more to 2x, 0.5x or more to less than 1.5x, 0.5x or more to 1.5x or less, 0.5x or more to 1.4x, 0.5x or more to 1.3x, 0.5x or more to 1.2x, 0.5x or more to 1.1x, 0.5x or more to 1x, 0.5x or more to 0.9x, 0.5 times or more to 0.8 times, 0.5 times or more to 0.7 times, 0.5 times or more to 0.6 times, 0.53 times or more to 6 times, 0.4 times or more to 5 times, 0.5 times or more to 5 times, 0.53 times or more to 5 times, 0.4 times or more to 4 times, 0.5 times or more to 4 times, 0.53 times or more to 4 times, 1.5 times or more to 10 times, 2 times or more to 10 times, 2 times or more to 4 times, preferably a allulose modified product, allulose modified polymer, or an intermediate substance generated and converted in the process of allulose decomposition, which has a molecular weight of 0.4 times or more to 4 times..
[0015] As an example, the aforementioned allulose conversion product (Impurity-S) is such that the more it is continuously exposed to external stimuli, such as high temperature or acidic conditions, the allulose modified polymer that is the allulose conversion product (Impurity-S) can also be converted into an allulose modified polymer (allulose tetramer analog) having a molecular weight close to that of a dimer. This is due to the mechanism that allulose is easily modified by external stimuli, so that random dehydration and condensation polymerization reactions with allulose or allulose conversion products are repeated, leading to conversion into the modified polymer as described above. Alternatively, the aforementioned allulose conversion product (Impurity-S) may be an intermediate substance generated and converted in the process of allulose decomposition.
[0016] Specifically, as a result of analysis by LC-MS, the component detected at a molecular weight of 341 m / z is a component that increases as the crystallization stock solution containing allulose is treated under harsh conditions, and it can be confirmed by molecular weight analysis that the substance has a dimer-like structure modified by dehydration or condensation reaction of allulose. This is the result of inferring the structure by LC-MS analysis, C 12 H 22 O 11 It is a substance with the chemical formula of, and can be predicted to be an allulose modified polymer. The more additional heat treatment is performed, C 25 H 28 O 11 , C 24 H 42 O 21 or C24 H 44 O 22 It was confirmed that the content of allulose-modified polymers (tetramer analogs of allulose) having a molecular weight similar to that of the allulose-modified polymer dimer also increased. This suggests that allulose is easily modified by external stimuli (stress), such as heat treatment, and random dehydration and condensation reactions are repeatedly carried out with allulose or allulose converters, converting it into the aforementioned substances.
[0017] Specifically, analysis by LC-MS revealed that the components detected as being present in the allulose converter (Impurity-S) may include furan aldehyde intermediates, which are produced during the decomposition of hexoses like allulose into HMF through dehydration reactions. + Ion-bonded form [C6H 12 O6+Na] + , or Na in the allulose dimer molecule + A molecule with bonded ions [C6H 12 O6+Na] + It may include.
[0018] Furthermore, LC-MS analysis revealed that the allulose converter has the molecular formula C x H y O z The compound may include the following, where x may be an integer from 3 to 15, an integer from 3 to 14, an integer from 3 to 13, an integer from 3 to 12, an integer from 4 to 15, an integer from 4 to 14, an integer from 4 to 13, an integer from 4 to 12, an integer from 5 to 15, an integer from 5 to 14, an integer from 5 to 13, or an integer from 5 to 12, where y may be an integer from 1 to 15, an integer from 1 to 14, an integer from 1 to 13, an integer from 1 to 12, an integer from 2 to 15, an integer from 2 to 14, an integer from 2 to 13, an integer from 2 to 12, an integer from 3 to 15, an integer from 3 to 13, an integer from 3 to 12, an integer from 4 to 15, an integer from 4 to 14, an integer from 4 to 13, or an integer from 4 to 12, where z may be an integer from 1 to 10, an integer from 1 to 9, an integer from 1 to 8, an integer from 1 to 7, or an integer from 1 to 6.
[0019] For example, allulose conversions include C5H4O3, C5H6O4, C5H8O3, C5H4O2, and C5H 10 O3, C6H4O5, C6H 10 O3, C6H4O4, C6H6O3, C6H8O, C6H4O5, C6H6O4, C6H4O4, C6H4O3, C6H8O3, C 11 H8O6, C 12 H 12 O5, or C 12 H 10 It may contain substances having the chemical formula O5.
[0020] Specifically, allulose conversions include levulinic acid (4-oxopentanoic), furfural, hydroxymethylfurfural (HMF), γ-hydroxyvaleric acid (GVB), 2,5-dimethylfuran, 2,5-furandicarboxylic acid (FDCA), 5-hydroxymethyl-2-furoic acid, 2,5-formylfurancarboxylic acid, 2,5-furandicarbaldehyde, 2,5-bis-(hydroxymethyl)furan, and bis(5-formyl-2-furfuryl) ether. It may contain one or more substances selected from the group consisting of ether, 2-furoic acid, 3-furoic acid, 5-Hydroxyfurfural, 2,5-Dihydro-2,5-dimethoxyfuran, (2R)-5-Oxotetrahydro-2-furancarboxylic acid, 2,5-formylfuran carboxylic acid, 5,5'-Methylenedi(2-furoic acid)), and bis(5-methyl furfuryl) ether.
[0021] The present invention provides a method for producing, separating, and / or purifying allulose under conditions that do not generate allulose converters, thereby removing or reducing the content of the converter (Impurity-S) contained in the allulose syrup, which is the raw material used in the allulose crystallization process. Therefore, by the method according to the present invention, the content of Impurity-S in the crystallization stock solution can be reduced, lowering the content of impurities that hinder crystal growth and improving crystal shape and crystal yield.
[0022] Specifically, the content of the conversion product (Impurity-S) can be adjusted by preventing or reducing the generation of Impurity-S, or by removing or reducing the generated Impurity-S. In one example of the present invention, as a method of controlling the allulose production process under conditions that prevent or reduce the generation of allulose conversion products, the allulose crystal grain size can be increased, the crystals can be formed into a shape close to a square, and the allulose yield can be improved. More specifically, by controlling the allulose conversion product (Impurity-S) component content in the crystallization stock solution to 2% by weight or less, allulose crystal particle growth and yield can be improved.
[0023] The method for preventing or reducing the generation of Impurity-S can be achieved by controlling the conditions of the allulose production process, particularly the pH, temperature, and electrical conductivity in the concentration step, under conditions that prevent the generation of allulose conversion products. Alternatively, the method for removing or reducing the generated Impurity-S can be a method of activated carbon treatment or a method of redissolving crystals obtained in primary crystallization and performing secondary crystallization, or a method for removing impurities from allulose syrup can be used.
[0024] Specifically, the method for generating or adjusting the content of impurities can be carried out by one or more of the following methods.
[0025] As an example, one method for preventing or reducing the formation of allulose conversion product (Impurity-S) in the allulose production process is to carry out the allulose production process at a pH of 4 or higher and / or at a temperature of 70°C or lower. Specifically, since the allulose is relatively stable under conditions of a pH of 4 to 7 or pH 4 to 6 and a temperature of 70°C or lower, preferably 60°C or lower, it is preferable to control the reaction solution temperature in the allulose production process, such as decolorization, ion purification, and high-purity separation, so as not to exceed 70°C, preferably 60°C, and in particular to control the concentration process by dividing it into two or more stages so as not to continuously expose it to external stimuli.
[0026] To prevent or reduce the generation of Impurity-S in the allulose production process, the concentration step can be carried out at a temperature of 40-70°C or lower on the allulose fraction obtained in the SMB chromatography separation step, and the concentration step can be selectively divided into at least two stages. For example, when the concentration step is divided into two stages, the allulose syrup can be primarily concentrated to a concentration of 30-50 Bx, and the primary concentrate can be concentrated twice more to a concentration of 60-85 Bx. Preferably, an activated carbon treatment step can be added between the primary and secondary concentration steps to remove or reduce the amount of Impurity-S contained in the concentrated water.
[0027] Another example of a method for removing or reducing the amount of impurity-S contained in allulose syrup, which is the raw material for allulose crystallization, is to treat it with activated carbon to adsorb and remove high-molecular-weight or low-molecular-weight organic substances, colored ionic substances, or proteins that act as impurities or induce allulose denaturation.
[0028] More specifically, the allulose fraction obtained by performing an SMB chromatography separation step on the allulose reaction solution obtained from the substrate can be treated with activated carbon before concentration to remove or reduce the content of the conversion product (Impurity-S). The activated carbon step can be performed additionally by subjecting the allulose fraction obtained in the SMB chromatography separation step to an ion purification step.
[0029] The activated carbon step involves contacting activated carbon with an allulose solution and reacting it at a temperature of 40-50°C for 0.5-5 hours. After that, the reaction solution containing the activated carbon is subjected to a solid-liquid separation step to obtain a filtrate, and impurities can be removed as filtration residue. This filtration can be performed using filtration equipment such as a filter press.
[0030] In the activated carbon reaction step, the reaction solution can be selectively stirred, and the stirring speed of the reaction solution may be 5 to 500 rpm, preferably 50 to 300 rpm. The stirring speed can be appropriately selected considering the degree of dispersion of the activated carbon and the cost required for stirring. The contact time between the activated carbon and the reaction solution can be appropriately selected considering the degree of dispersion of the activated carbon and the efficiency of impurity removal, for example, it may be 0.5 to 5 hours, preferably 0.5 to 2 hours. If the contact time is too short, impurity removal, such as decolorization, will not be sufficient, and if the contact time is too long, the main components will be destroyed and browning will occur.
[0031] The activated carbon used in the activated carbon treatment process may be of coal or woody origin, and impurities can be selectively removed depending on the pore size of the activated carbon.
[0032] As an additional example, a method to prevent or reduce the formation of allulose conversion products (Impurity-S) in an allulose crystallization composition is to perform recrystallization. Primary crystallization is performed with an allulose solution that has undergone a high-purity separation and concentration process. The supernatant is removed from the primary crystallization stock solution, the allulose crystals are dehydrated and recovered, and then the allulose crystals are dissolved in water again to produce an allulose solution for crystallization. This solution is then added to the secondary crystallization process, thereby removing or reducing the allulose conversion product (Impurity-S) content in the primary crystallization process.
[0033] Therefore, one example of the present invention provides a method for adjusting the content of allulose converter (Impurity-S) contained in an allulose composition for crystallization to 2% by weight or less, based on the solid content of the composition.
[0034] The above method can be carried out by adjusting one or more conditions selected from the group consisting of pH conditions and temperature conditions of the composition, wherein the pH conditions may be in the range of pH 4 to 7 and the temperature conditions may be 70°C or lower.
[0035] The crystallization allulose composition can be produced by concentrating an allulose solution obtained by treating an allulose-containing reaction solution in an SMB chromatography separation step at a temperature of 40 to 70°C or lower. The concentration step can be divided into at least two stages, with the allulose solution being primarily concentrated to a concentration of 30 to 50 Bx, and the primary concentrate being concentrated twice more to a concentration of 60 to 85 Bx. An activated carbon treatment step can be added before the concentration step.
[0036] Another example of the present invention relates to an allulose crystallization composition containing an allulose converter (Impurity-S) content of 2% by weight or less, 1.9% by weight or less, 1.8% by weight or less, 1.7% by weight or less, 1.6% by weight or less, 1.5% by weight or less, 1.4% by weight or less, 1.3% by weight or less, 1.2% by weight or less, 1.1% by weight or less, 1.0% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.65% by weight or less, 0.6% by weight or less, 0.5% by weight or less, 0.4% by weight or less, 0.3% by weight or less, 0.2% by weight or less, 0.1% by weight or less, preferably 1.0% by weight or less, based on 100% by weight of the total solids content of the composition, and is even more preferably free of impurities.
[0037] Preferably, the allulose crystallization composition may contain an allulose content of 90% by weight or more, 91% by weight or more, 92% by weight or more, 93% by weight or more, 94% by weight or more, or 95% by weight or more, based on 100% by weight of the total solid content of the composition.
[0038] The viscosity of the allulose crystallization composition may be 2 cps to 200 cps at a composition temperature of 45°C, and the electrical conductivity may be 1,000 uS / cm or less, for example 0.01 to 1,000 uS / cm, preferably 30 uS / cm or less, for example 0.1 to 30 uS / cm. A lower electrical conductivity of the allulose crystallization composition is preferable for crystallization. The electrical conductivity of the allulose syrup is a value measured based on a solid content of 30Bx.
[0039] The allulose solution for crystallization may have a solid content of 60 to 85 Brix, for example, greater than 60 Brix to 80 Brix, 65 to 85 Brix, 65 to 80 Brix, or 68 to 85 Brix.
[0040] An example of the present invention relates to a method for producing allulose crystals using an allulose solution for crystallization, and more specifically, to a method for producing allulose crystals comprising the steps of: providing an allulose crystallization composition containing an allulose converter (Impurity-S) content of 2% by weight or less, 1.9% by weight or less, 1.8% by weight or less, 1.7% by weight or less, 1.6% by weight or less, 1.5% by weight or less, 1.4% by weight or less, 1.3% by weight or less, 1.2% by weight or less, 1.1% by weight or less, preferably 1.0% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.65% by weight or less, 0.6% by weight or less, 0.5% by weight or less, 0.4% by weight or less, 0.3% by weight or less, 0.2% by weight or less, 0.1% by weight or less, based on 100% by weight of the total solid content of the composition; and cooling the aqueous allulose solution to produce allulose crystals.
[0041] In one specific example of the present invention, a method for producing allulose crystals includes a step of purifying the allulose fraction obtained in an SMB chromatography separation step with secondary ions, a step of concentrating the ion-purified allulose fraction, and a step of crystallizing allulose from the concentrate to obtain allulose crystals and allulose crystal mother liquor, and may optionally include steps of recovering the allulose crystals, washing, and drying.
[0042] Furthermore, the allulose fraction obtained in the SMB chromatography separation step, or the solution obtained by ion-purifying the allulose fraction, can be treated with activated carbon before the concentration step to reduce or remove the allulose conversion product (Impurity-S). Alternatively, after concentrating the allulose solution for crystallization, primary crystallization can be performed, and the resulting crystals can be dissolved and crystallized a second time to reduce or remove the allulose conversion product (Impurity-S).
[0043] In one specific example of the present invention, a method for producing the crystallization allulose composition includes a step of second ion purification of the allulose fraction obtained by treating the allulose-containing reaction solution produced from the substrate in an SMB chromatography separation step, and a step of concentrating the ion-purified allulose fraction, or it may include an ion purification step, an activated carbon treatment step, or both of the activated carbon treatment step and the ion purification step for treating the allulose fraction obtained by treating it in the SMB chromatography separation step.
[0044] The step of providing the allulose composition for crystallization relates to a method for producing allulose crystals such that, based on 100% by weight of the total solid content contained in the crystallization composition, the allulose conversion (Impurity-S) content is 2% by weight or less, 1.9% by weight or less, 1.8% by weight or less, 1.7% by weight or less, 1.6% by weight or less, 1.5% by weight or less, 1.4% by weight or less, 1.3% by weight or less, 1.2% by weight or less, 1.1% by weight or less, 1.0% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.65% by weight or less, 0.6% by weight or less, 0.5% by weight or less, 0.4% by weight or less, 0.3% by weight or less, 0.2% by weight or less, 0.1% by weight or less, preferably 1.0% by weight or less, or preferably does not contain any allulose conversion (Impurity-S).
[0045] The method for producing allulose crystals according to the present invention may yield allulose crystals with an allulose crystal yield of 45% or more, preferably 48% or more, 50% or more, 53% or more, 54% or more, more preferably 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, or 60% or more.
[0046] The allulose converter content can be adjusted by adjusting one or more of the following: pH conditions and the temperature of the allulose solution. The pH adjustment can be achieved in the range of pH 4 to 7, pH 4.5 to 7, or pH 5 to 7, preferably pH 5 to 7. The temperature of the solution can be adjusted to a range of 80°C or less, 75°C or less, 70°C or less, preferably 30 to 70°C or less, 30 to 69°C, 30 to 65°C, or 30 to 60°C.
[0047] Because allulose is unstable at lower pH and higher temperatures, its content changes during the actual production process, particularly during the concentration stage. This problem reduces the purity of the allulose solution and significantly affects the crystallization stage. We confirmed that while the allulose content decreases during this process, the content of a specific allulose converter (Impurity) that is additionally produced increases, and this component significantly affects allulose crystallization. We found that when the content of Impurity-S, among the various allulose converters, exceeds 2%, it acts as a major inhibiting factor for the growth of allulose crystal particles, and therefore significantly affects the particle size and crystallization yield.
[0048] Specifically, as shown in Figures 1 and 2, the allulose content decreased and the allulose conversion product (Impurity-S) content increased as the storage temperature increased. As shown in Figures 3 and 4, at a temperature of 70°C, the allulose content decreased and the amount of allulose conversion product produced increased as the pH decreased.
[0049] The allulose composition for crystallization according to the present invention may be a reaction product containing allulose obtained by a biological or chemical process, an allulose fraction obtained by SSMB chromatography separation of the reaction product, or a concentrate obtained by concentrating the allulose fraction. An additional ion purification and / or activated carbon treatment step may be performed before the concentration step for producing the allulose concentrate, and the concentration step may also be divided into at least two steps. The allulose-containing reaction product can be obtained from a fructose substrate by a biological or chemical method, preferably by a biological method using allulose convertase or a microorganism that produces the enzyme.
[0050] The allulose reaction solution can undergo a separation process for the psicose conversion reaction product, which includes ion purification and pseudo-mobility bed (SMB) chromatography separation. In a specific example, the psicose conversion reaction product is subjected to ion purification and SMB chromatography separation to separate it into a psicose fraction with a higher psicose content and a fructose raffinate. The psicose fraction is then subjected to a psicose concentration process before being introduced into a crystallization process.
[0051] To obtain allulose crystals, the allulose content in the allulose solution must be high in a supersaturated state. However, since the allulose content of the allulose conversion reaction product is low, direct crystallization cannot be performed. Therefore, before the crystallization stage, a process must be carried out to purify the allulose and concentrate it to the desired level in order to increase its content.
[0052] The method for obtaining the above composition can be carried out by performing a concentration step at a temperature of 90°C or lower, 85°C or lower, 80°C or lower, 75°C or lower, 70°C or lower, or less than 70°C, for example, 40°C or higher, or 70°C or lower, and can be specifically carried out using a thin-film concentrator or a multiple-effect evaporator. In one specific example of the present invention, the step of concentrating the purified allulose solution can be carried out under temperature conditions of 40 to 70°C or lower. If the temperature of the concentrated solution is above 70°C, thermal denaturation of D-allulose may occur, and as a result, the allulose converter (Impurity-S) according to the present invention may be generated or increased. Also, since the temperature of the reactants increases rapidly due to the heat of vaporization when concentration is performed, the concentration must be carried out quickly while maintaining the temperature of the concentrated solution at 70°C or lower.
[0053] Specifically, the concentration step of the allulose fraction obtained in the SMB chromatography separation step can be carried out by various methods, and the solid content of the concentrate can be made to 70 Brix or more. For example, the allulose fraction obtained by the pseudo-mobile bed adsorption separation method (e.g., solid content of 20-30% by weight) can be concentrated to a solid content of 60 Brix or more by the concentration step. The allulose crystallization composition according to the present invention may have a solid content of 60 or more and 85 Brix (Bx) or less, for example, greater than 60 Brix to 85 Brix, 65 to 85 Brix, 70 to 85 Brix, 75 to 85 Brix, greater than 60 Brix to 83.5 Brix, 65 to 83.5 Brix, 70 to 83.5 Brix, or 75 to 83.5 Brix.
[0054] As an example, the crystallization composition may be an allulose fraction obtained by performing a simulated moving bed (SMB) chromatography separation step using a column chromatograph packed with a cation exchange resin to which calcium active groups are attached. Specifically, it may be an allulose fraction obtained by using a biological catalyst to convert a fructose-containing raw material to allulose, obtaining an allulose conversion reaction product, and then performing activated carbon treatment, ion purification, and simulated moving bed (SMB) chromatography separation steps on the allulose conversion reaction product. The allulose fraction may be obtained either directly from the SMB chromatography separation step or through the ion purification step. The fructose content of the fructose-containing raw material may be 85% by weight or more based on 100% by weight of the total solid content of the fructose-containing raw material, and a biological catalyst may be used that has an allulose conversion rate of 15% to 70% in the allulose conversion reaction.
[0055] The allulose fraction obtained in the SMB chromatography separation step can be subjected to an additional ion purification and / or activated carbon treatment step before the concentration step.
[0056] The method for producing allulose crystals according to the present invention allows for crystallization by adjusting the temperature and concentration of the allulose concentrate solution. Specifically, the supersaturated state required for crystallization can be maintained by lowering the temperature of the allulose solution or changing the concentration of D-allulose in the D-allulose solution. In one specific example of the present invention, the crystallization process can be monitored by taking samples at regular intervals during the crystallization stage and observing them with the naked eye or under a microscope, or by analyzing the sugar concentration in the upper layer liquid obtained from centrifugation of the sample. Based on the results, the temperature or the concentration of D-allulose can be adjusted. When crystallizing an allulose concentrate solution by cooling it to produce allulose crystals, crystal growth can be induced by rapidly cooling it to a temperature range of 10-25°C using a heat exchanger, followed by repeated heating and cooling.
[0057] The method for producing allulose crystals according to the present invention allows for crystallization by adjusting the temperature and concentration of the allulose concentrate solution. Specifically, the supersaturated state required for crystallization can be maintained by lowering the temperature of the allulose solution or by changing the concentration of D-allulose in the D-allulose solution. The method for producing allulose crystals according to the present invention can be carried out in various ways, preferably by a cooling method. One example of the cooling method according to the present invention is to cool the allulose solution to a temperature of 35 to 10°C to induce a supersaturated state and generate crystals. It is preferable to maintain a cooling rate of 0.01 to 20°C / min. If the cooling rate is low, the cocrystal formation time is long and productivity is low, and if the cooling rate is high, crystals with small particle sizes are formed and it is difficult to recover the crystals.
[0058] The method for producing the allulose crystal may include the steps of generating crystal nuclei in an allulose solution containing 90% by weight or more of allulose and having an electrical conductivity of 1,000 uS / cm or less with a Brix value of 60 to 85, and growing crystals by cooling the temperature of the solution.
[0059] Specifically, the method for producing allulose crystals may include the steps of generating crystal nuclei by slowly stirring an allulose solution containing 90% by weight or more of allulose at a concentration of 60 to 85 Brix at a temperature of 20 to 40°C or 30 to 40°C, for example, 35°C, and growing crystals by cooling the temperature of the solution to 10°C. The method may further include one or more steps of increasing the temperature of the solution to a range of 30 to 35°C and redissolving the fine crystals generated during the cooling process. The method for producing allulose crystals may further include the step of adding the seed crystal. The seed crystal addition step and the redissolution step may be selectively included in the method for producing allulose crystals, or both steps may be included.
[0060] It is generally known that the larger the size of the allulose crystal, the better its physical properties and the greater its usability. To produce such large crystals, it is necessary to carry out both the seed crystal transfer process and the main crystallization process. However, the crystallization process according to the present invention can easily produce relatively large crystals in high yield in a single step.
[0061] Furthermore, the crystallization step can be performed by raising the temperature of the solution to 30-35°C to dissolve the microcrystals that were generated during the cooling process in the crystal growth step. In the crystallization step according to the present invention, the crystal growth step and the microcrystal dissolution step can be repeated at least once.
[0062] In the process of producing the aforementioned crystals, seed crystals may be added in order to increase the crystal growth rate and size.
[0063] In a specific example according to the present invention, allulose crystals can be produced by slowly stirring an allulose solution containing 90% by weight or more of allulose on a solids basis and having a total solids content of 60 to 85 Brix at a temperature of 35°C to generate a small amount of crystal nuclei, then cooling the solution to 10°C by decreasing the temperature by 1°C per hour to grow the crystals, and then repeating the process of raising the temperature of the solution to 30 to 35°C to dissolve the fine crystals that were selectively formed during the cooling process at least once.
[0064] The method for producing allulose crystals according to the present invention may further include a step of recovering the allulose crystals obtained in the crystallization step by various solid-liquid separation methods, such as centrifugation, a step of washing with deionized water, and a step of drying. The drying step is carried out in a fluidized bed dryer or a vacuum dryer, but is not limited thereto.
[0065] Allulose crystals can be produced by a method of cooling the allulose crystallization composition according to the present invention. The allulose crystallization composition is as described above.
[0066] The allulose contained in the allulose crystal may be 94% or more by weight, 95% or more by weight, 96% or more by weight, 97% or more by weight, 98% or more by weight, or 99% or more by weight, based on a total solid content of 100% by weight.
[0067] In this invention, "crystal purity" refers to the purity of the allulose crystals. The physical properties, including the purity of the crystals in this invention, can be determined by methods such as X-ray powder diffraction analysis, differential scanning calorimetry (DSC) analysis, infrared spectroscopy (FTIR) analysis, HPLC analysis, and LC / MS analysis, and the purity can be specifically analyzed by HPLC chromatography.
[0068] An example of the present invention may be an allulose crystal having an X-ray spectral spectrum with peaks at diffraction angles (2θ) ±0.2° at 15.24, 18.78, and 30.84. In an example of the present invention, the X-ray spectral spectrum may be an allulose crystal having an X-ray spectral spectrum with peaks at diffraction angles (2θ) ±0.2° at 15.24, 18.78, 30.84, and 28.37, at diffraction angles (2θ) ±0.2° at 15.24, 18.78, 30.84, and 31.87, or at diffraction angles (2θ) ±0.2° at 15.24, 18.78, 30.84, and 47.06. The diffraction angles with peaks in the X-ray spectral spectrum of the allulose crystal are displayed by selecting the main peaks and morphologically specific peaks from the X-ray diffraction analysis results (relative intensity%).
[0069] The allulose crystals according to the present invention can be obtained by various crystallization methods, but the properties measured may be those of allulose crystals produced by the cooling method.
[0070] An allulose crystal according to an example of the present invention can have a Tm temperature of 125.8°C ± 5°C or a melting enthalpy (ΔH) of 200-220 J / g as determined by DSC analysis, and the Tm may be 125.8°C ± 3°C. Differential scanning thermal analysis (DSC) is operated by a temperature gradient and measures the energy provided to maintain the temperature rise of the allulose powder sample. DSC analysis of a crystal shows that the higher the heat capacity, the less easily it melts, and the higher the heat capacity and the narrower the endothermic peak width, the more uniform and robust the crystal formation can be predicted.
[0071] Another example of the present invention is an allulose crystal produced with the allulose crystallization composition, which preferably has one or more properties selected from the group consisting of (1) to (5) below: (1) Having a powder X-ray spectroscopy spectrum with peaks at diffraction angles (2θ) ±0.2° at 15.24, 18.78, and 30.84 degrees, (2) A Tm temperature of 125.8°C ± 5°C is determined by differential scanning thermal analysis (DSC). (3) Differential scanning thermal analysis reveals that the enthalpy of fusion (ΔH) is 200-220 J / g. (4) Having an average major diameter of 350 μm or more, preferably 350 to 2,000 μm, (5) The ratio of the major diameter length (micrometers) to the minor diameter of the allulose crystal (= major diameter / minor diameter) falls within the range of 1.0 to 8.0.
[0072] The allulose crystal according to the present invention may have an average short diameter of 50 to 1,000 μm, preferably 50 to 500 μm, and an average long diameter of 350 μm or more, preferably 350 to 2,000 μm, and more preferably 400 μm to 2,000 μm.
[0073] Furthermore, the ratio of the length (micrometers) of the major diameter to the minor diameter (= major diameter / minor diameter) of the allulose crystal according to the present invention can be 1.0~8.0, 1.0~6.9, 1.0~6.0, 1.0~5.5, 1.0~5.0, 1.1~8.0, 1.1~6.9, 1.1~6.0, 1.1~5.5, 1.1~5.0, 1.3~8.0, 1.3~6.9, 1.3~6.0, 1.3~5.5, 1.3~5.0, 1.5~8.0, 1.1~6.9, 1.5~6.0, 1.5~5.5, 1.5~5.0, 2.0~8.0, 2.0~6.9, 2.0~6.0, 2.0~5.5, and 2.0~5.0.
[0074] According to the results of powder XRD pattern analysis of allulose crystals according to the present invention, the allulose crystals according to the present invention have a rectangular hexahedron or a structure close to it as pure crystal particles. The closer the crystal structure of the present invention is to a cubic crystal system, the higher the uniformity and rigidity of the crystal, which is therefore preferable.
[0075] Furthermore, the more uniform the crystals produced in the allulose crystallization process, the higher the crystal strength and the less particle breakage occurs, resulting in a more uniform particle size distribution and improved flowability. On the other hand, if the uniformity is low, the crystal particles become undifferentiated due to breakage during the drying and transport stages, making them relatively easy to dissolve and thus negatively impacting product quality.
[0076] The allulose crystals of the present invention have better flowability compared to fine powder form, are less prone to caking, are stable during storage, and have the characteristics of being easy to distribute and handle. Furthermore, since the allulose powder has a lower calorie content than sugar and a sweetness similar to sugar, it can be easily and advantageously manufactured in the form of mixed sweeteners, solid mixed sweeteners, chocolate, chewing gum, instant juices, instant soups, granules, and refined products. In addition, the allulose crystal powder can be contained and used in various compositions such as food and beverages, condiments, animal feed, cosmetics, and pharmaceuticals. [Effects of the Invention]
[0077] The method for producing allulose crystals according to the present invention can prevent the size of allulose particles from becoming too small by controlling the content of allulose converter (Impurity-S) in the solution used to produce the crystals, and can produce allulose with uniform particle size by appropriately adjusting the crystal particle growth. Furthermore, by growing the particles to a uniform size, losses in the recovery process can be reduced, improving the crystal yield and increasing productivity. [Brief explanation of the drawing]
[0078] [Figure 1] This graph shows the change in allulose content when allulose syrup with a pH of 5 and a Brix concentration of 70 is stored at different temperatures. [Figure 2] This graph shows the change in the content of allulose converters when allulose syrup with a pH of 5 and a Brix concentration of 70 is stored at different temperatures. [Figure 3] This graph shows the change in allulose content when allulose syrups with different pH levels and a Brix concentration of 70 are stored at a temperature of 70°C. [Figure 4] This graph shows the change in the content of allulose converters when allulose syrups with different pH levels and a Brix concentration of 70 are stored at a temperature of 70°C. [Figure 5] This is an optical microscope image of the allulose powder obtained in Example 5, measured at a magnification of X100. [Figure 6] This is a scanning electron microscope (SEM) image of the allulose powder obtained in Example 5, measured at a magnification of X50. [Modes for carrying out the invention]
[0079] The present invention will be further described in detail by the following examples. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited thereto. [Examples]
[0080] Example 1: Production of allulose crystals Allulose syrup was produced from a fructose substrate by a biological method substantially identical to the manufacturing method described in Korean Published Patent No. 2014-0054997. The allulose syrup was desalted by passing it through a room-temperature column packed with cation exchange resin, anion exchange resin, and a resin mixed with cation and anion exchange resin at a rate of twice the volume of ion exchange resin per hour (1-2 times), in order to remove impurities such as colored and ionic components. 2+ The results were separated and obtained using a high-purity allulose solution with chromatography packed with a type of ion exchange resin. The high-purity allulose syrup containing 97% by weight of allulose, obtained by the high-purity separation process (SMB), was primary concentrated to a concentration of 35 Bx (w / w%) and then secondary concentrated to produce an allulose syrup for crystallization containing 97% by weight of allulose, with a concentration of 81 Bx (w / w%) and an electrical conductivity of 12 uS / cm. The electrical conductivity of the allulose syrup was measured based on a solid content of 30 Bx. The concentrated allulose syrup was gradually cooled from a supersaturated temperature of 35°C to 10°C to grow crystals. During this process, allulose seed crystals were added and slowly stirred at 35°C to generate a small amount of crystal nuclei. Then, the temperature was decreased by 1°C per hour to grow the crystals. In order to redissolve the fine crystals that had formed during the cooling process in the crystal growth step, the temperature of the solution was raised to 30-35°C to dissolve the fine crystals. The crystal growth step and the fine crystal dissolution step were repeated at least once to complete the crystallization. The allulose crystals produced were collected after removing the mother liquor by centrifugal dehydration, washing the crystals with cooling water, and drying them.
[0081] The allulose content and allulose conversion product (Impurity-S) content of the aforementioned crystallization stock solution, as well as the purity of the allulose crystals, were determined by the following HPLC analysis. The analytical conditions were as follows: Analysis column: Biolad Aminex HPX-87C column Mobile phase: water Flow rate: 0.6 ml / min Column temperature: 80℃ Detector: RI detector
[0082] Based on the results of the HLPC analysis, using a solid content of 100% by weight of the allulose aqueous solution for crystallization as a baseline, the allulose conversion product (Impurity S) content of the allulose aqueous solution for crystallization was 0.4% by weight, and the allulose content was 97.0% by weight. The allulose crystal yield produced by the above method was 63.6%. The crystal water content is expressed as a percentage of the weight of the recovered allulose crystal powder after dehydration and washing relative to the solid content weight of the allulose syrup used as a raw material for crystallization.
[0083] Examples 2 and 3: Preparation of allulose crystals A method substantially similar to that used for allulose production in Example 1 was carried out, and by a high-purity separation step (SMB), a high-purity allulose syrup containing 96.6% by weight of allulose was obtained in Example 2 at a concentration of 35 Bx (w / w%), a high-purity allulose syrup containing 95.8% by weight of allulose was concentrated in Example 3 to obtain a concentration of 35 Bx (w / w%), and a high-purity allulose syrup containing 95.5% by weight of allulose was concentrated in Example 6 to obtain a concentration of 35 Bx (w / w%). The allulose solution was concentrated to produce an allulose syrup for crystallization with a concentration of 81Bx (w / w%) containing 96.6% by weight of allulose and an electrical conductivity of 14 uS / cm in Example 2, an allulose syrup for crystallization with a concentration of 81Bx (w / w%) containing 95.8% by weight of allulose and an electrical conductivity of 14 uS / cm in Example 3, and an allulose syrup for crystallization with a concentration of 81Bx (w / w%) containing 95.5% by weight of allulose and an electrical conductivity of 12 uS / cm in Example 6. The electrical conductivity of the allulose syrup was measured based on a solid content of 30Bx. Crystallization was carried out using the concentrated allulose syrup with the same crystallization method as in Example 1, and the crystals were washed with cooling water, dried, and recovered. The allulose content of the crystallization stock solution, the allulose conversion product (Impurity-S) content, and the purity of the allulose crystals were determined by HPLC analysis using the same method as in Example 1. The results are shown in Table 1 below. Specifically, the allulose crystal yield produced with the allulose syrup for crystallization of Example 2 (allulose converter content 0.3% by weight, allulose content 96.6% by weight) was 61.9%, the allulose crystal yield produced with the allulose syrup for crystallization of Example 3 (allulose converter content 0.5% by weight, allulose content 95.8% by weight) was 61.6%, and the allulose crystal yield produced with the allulose syrup for crystallization of Example 6 (allulose converter content 0.25% by weight, allulose content 95.5% by weight) was 62.1%.
[0084] Example 4: Preparation of Allulose Crystals A method substantially similar to that used for allulose production in Example 1 was followed, and a high-purity allulose syrup containing 97.0% by weight of allulose was obtained at a concentration of 35 Bx (w / w%) by a high-purity separation step (SMB). To minimize impurities contained in the allulose syrup, it was treated with activated carbon suitable for impurity removal at a temperature of 40°C for 30 minutes, and then filtered. The allulose syrup after activated carbon treatment was concentrated to a concentration of 81Bx (w / w%) to produce an allulose syrup for crystallization containing 97.3% by weight of allulose and having a concentration of 81Bx (w / w%) and an electrical conductivity of 10 uS / cm. The concentrated allulose syrup was gradually cooled from a supersaturated temperature of 35°C to 10°C to grow crystals. During this process, allulose seed crystals were added and slowly stirred at 35°C to generate a small amount of crystal nuclei. Then, the temperature was decreased by 1°C per hour to grow the crystals. In order to redissolve the fine crystals that had formed during the cooling process in the crystal growth step, the temperature of the solution was raised to 30-35°C to dissolve the fine crystals. The crystal growth step and the fine crystal dissolution step were repeated at least once to complete the crystallization. The allulose crystals produced here were dehydrated by centrifugation to remove the mother liquor, washed with cooling water, dried, and recovered.
[0085] Example 5: Production of allulose crystals A method substantially similar to that used for allulose production in Example 1 was carried out, and a high-purity allulose syrup containing 97.0% by weight of allulose was concentrated by a high-purity separation step (SMB) to obtain a concentration of 35 Bx (w / w%). The allulose syrup was concentrated to a high-purity allulose syrup containing 97% allulose by weight, based on a solid content of 100% by weight, and concentrated to a concentration of 81 Bx (w / w%) to produce an allulose syrup for crystallization with an electrical conductivity of 8 uS / cm. Crystallization was carried out using the concentrated allulose syrup with the same crystallization method as in Example 1, and the crystals were washed with cooling water, dried, and recovered. The primary crystal obtained above was dissolved in water to prepare allulose solution 81.2Bx, and the allulose solution was analyzed by the HPLC analysis method of Example 1. The results showed that the allulose conversion product (Impurity S) content was 0.07% by weight and the allulose content was 99.5% by weight. As a raw material for the secondary crystallization process, the allulose solution produced above was used, and the secondary crystallization process was carried out in substantially the same manner as the primary crystallization method. The allulose crystals produced here were dehydrated by centrifugal dehydration to remove the mother liquor, and the final crystals obtained by secondary crystallization were washed with cooling water, dried, and recovered to produce secondary crystals. The yield of secondary crystals was 62.5%.
[0086] [Table 1]
[0087] As shown in Table 1 above, compared to the allulose crystal yields of Examples 1 to 3, which exceeded 60%, Comparative Example 1, even with a high allulose content in the crystallization stock solution, failed to produce proper crystals if the allulose conversion product (Impurity-S) content exceeded 2% by weight, resulting in a significant reduction in crystal yield due to the small size of the crystals.
[0088] Comparative Example 1: Production of allulose crystals when the allulose conversion content exceeds 2% by weight. To investigate the allulose crystal yield when the allulose conversion content of the crystallization stock solution exceeds 2% by weight, acidic pH conditions or heat treatment conditions were applied to the crystallization stock solution for secondary crystallization in Example 5 to induce allulose conversion. Specifically, a crystallization stock solution for secondary crystallization was prepared by dissolving the allulose crystals obtained by primary crystallization in Example 5 in water, and then heat-treating it for 3 hours under conditions of pH 3.5 and temperature 80°C to produce a crystallization stock solution. Crystallization was performed using the concentrated allulose syrup with the same crystallization method as in Example 1, and the crystals were washed with cooling water, dried, and recovered. Using the same method as in Example 1, the allulose content of the crystallization stock solution, the allulose conversion product (Impurity-S) content, and the purity of the allulose crystals were determined by HPLC analysis as described below, and the results are shown in Table 2.
[0089] Comparative Example 2 and Examples 7-8: Production of allulose crystals based on allulose converter content In Example 5, allulose crystals obtained by primary crystallization were dissolved in water to produce a crystallization stock solution for secondary crystallization. This stock solution was then heat-treated at pH 4.5 and 70°C for 6, 13, or 24 hours to produce another crystallization stock solution. The allulose content and allulose converter content in the crystallization stock solution are shown in Table 2 below. The method for crystallizing using the prepared crystallization stock solution was substantially the same as in Example 1. Specifically, Comparative Examples 2 and Examples 7-8 were prepared using different heat treatment times to produce crystallization stock solutions having the allulose content and allulose converter content shown in Table 2 below, and the allulose crystallization process was carried out. The allulose content of the crystallization stock solution, the allulose conversion product (Impurity-S) content, and the purity of the allulose crystals were determined by HPLC analysis using the same method as in Example 1. The results are shown in Table 2 below.
[0090] [Table 2]
[0091] In Comparative Example 2, the crystallization stock solution had low allulose purity and a high allulose converter content, resulting in poor crystal growth and the formation of fine crystals, which were extremely difficult to dehydrate and wash. In Comparative Example 1, similar to Comparative Example 2, it was confirmed that the higher the allulose converter content, the less successful the crystal size growth and the more fine crystals were formed. In Examples 7 and 8, it was confirmed that a higher crystal yield was observed compared to the comparative examples when the allulose converter content was less than 2% by weight.
[0092] Experimental Example 1: LC-MS analysis of allulose conversion product (Impurity S) (1) Analysis of the allulose conversion product (Impurity S) of Example 2 In the HPLC analysis of the allulose syrup used for crystallization in Example 2, the impurity fraction separated at a peak with an elution time of 31 ± 2 minutes was directly obtained. The diluted solution from the separation fractionation was freeze-dried and concentrated to approximately 100 times its original concentration for analysis. The molecular weight of the impurities was analyzed using a liquid chromatography / mass spectrometer (LC / MS system, model name: LTQ, manufacturer: Thermo Finnigan, USA). The molecular weight of the allulose conversion product (Impurity S) measured by LC / MS analysis was found to be in the range of 300-400 m / z (mass / charge ratio).
[0093] (2) Analysis of allulose conversions (Impurity S) of Comparative Example 2 and Examples 7-8 In substantially the same manner as the LC-MS analysis method described above, the heat-treated crystallized stock solutions used in Comparative Example 2 and Examples 7-8 were used for LC-MS analysis in the HPLC analysis. LC-MS analysis was performed to determine the molecular weight changes of allulose and allulose converters due to the heat treatment, and the results of the analysis of the allulose content and allulose converter content (%) in the crystallized stock solutions used in Comparative Example 2 and Examples 7-8 are shown in Table 3 below. Table 3 below shows the LC-MS analysis data for allulose syrups with different heat treatment times (Example 7, Example 8, Comparative Example 2). The table shows the area values of the peaks detected for each molecular weight (m / z), converted to percentages. In Row 1 of Table 3, a molecular weight of 179.1 m / z is allulose. In Table 3 below, Rows 4, 8, and 10 show an increase in the allulose conversion product (Impurity S) content after heat treatment, while the remaining rows show a decrease in the allulose conversion product (Impurity S) content after heat treatment.
[0094] [Table 3]
[0095] As shown in the analysis results above, it was confirmed that the allulose content decreased and the impurity content increased as the heat treatment time increased, as measured by molecular weight analysis. In Row 1 of Table 3, the molecular weight of 179.1 m / z is allulose, and it was confirmed that the peak area value decreased after heat treatment. On the other hand, the component detected at a molecular weight of 341 m / z (Row 5 of Table) is a component that increases as the crystallized stock solution containing allulose is heat-treated, and molecular weight analysis confirmed that it is a substance with a dimer-like structure that has been modified by dehydration or condensation reaction of allulose. This was determined by inferring the structure from LC-MS analysis. 12 H 22 O 11 A substance with the chemical formula can be predicted to be an allulose-modified polymer. The more additional heat treatment is performed, the higher the C 25 H 28 O 11 , C 24 H 42 O 21 or C 24 H 44 O 22It was confirmed that the content of allulose-modified polymers (tetramer analogs of allulose) having a similar molecular weight to the dimer of the allulose-modified polymer also increased. This suggests that allulose is easily modified by external stimuli (stress), for example, by acidic pH and / or heat treatment in Comparative Examples 1 or 2, and undergoes repeated random dehydration and condensation reactions with allulose or allulose converters to convert them into the aforementioned substances.
[0096] (3) Analysis of allulose conversion product of Example 3 In the HPLC analysis of the allulose syrup used for crystallization in Example 3, the impurity fraction separated at a peak with an elution time of 31±2 minutes was directly obtained. The diluted solution from the separation fractionation was freeze-dried and concentrated to approximately 100 times its original concentration for analysis. We performed molecular weight analysis of allulose conversions using a liquid chromatograph / mass spectrometer (LCMS). -Equipment product name: Ultimate-3000 ISQ EC (Thermo Fisher) -Analysis column: Bio-rad Aminex HPX-87C - Column temperature: 80℃ -Flow rate: 0.3mL / min - Solvent: Distilled water -Injection volume: 5μl LC / MS analysis of the allulose convertible showed peaks around 55.22 m / z, 60.24 m / z, 74.14 m / z, 79.25 m / z, 82.22 m / z, 83.23 m / z, 109 m / z, 117 m / z, 124.26 m / z, 127.1 m / z, 141.5 m / z, 144 m / z, 163.23 m / z, 203.16 m / z, and 365.16 m / z, with the main peaks being around 127 m / z, 163 m / z, 198.2-203 m / z, and 365 m / z. Therefore, allulose converters are molecules composed of C, H, and O with 5 to 12 carbon atoms, and have a molecular weight charge value (m / z) of 50 to 400. They are modified substances derived from allulose and contain HMF and levulinic acid components, as well as derivative substances containing a Furan structure. Specifically, the 163 m / z peak is thought to be an intermediate substance (Furan aldehyde intermediate) produced in the process of decomposing hexoses like allulose with HMF through a dehydration reaction, while the 198.2 to 203 m / z peak is a form in which Na+ ions are bonded to the allulose molecule [C6H 12 O6+Na] + It is thought to be a molecule, and in the case of the 365 m / z peak, Na is present in the allulose dimer molecule. + [C6H] is bonded to an ion. 12 O6+Na] + It was thought to be a molecule. Based on the LC / MS analysis results of the allulose conversion, the compounds contained in the allulose conversion are shown in Table 4 below.
[0097] [Table 4]
[0098] (4) LC / MS analysis of 5-HMF LC / MS analysis of 5-HMF confirmed that the allulose conversion product contains 5-HMF. For the 5-HMF analysis sample, we purchased and used the standard substance (SIGMA-ALDRICH, CAS Number 67-47-0). As a result, the molecular weight m / z values of structures that can be produced by charge transfer, detachment, and dehydration reactions in aqueous solution of 5-HMF were shown, with peaks at 79.09 m / z, 109 m / z, 124.22 m / z, 127 m / z, and 144.15 m / z. The LC / MS analysis results partially matched those of the allulose conversion, confirming that the allulose conversion contains 5-HMF.
[0099] Experimental Example 2: Stability Analysis of Allulose To test the effects of temperature on allulose and allulose conversion water, 30g portions of allulose syrup containing 97% by weight of allulose from Example 1 were divided and stored in separate constant-temperature water baths at different temperatures. Samples were taken at different times and the changes in content were analyzed. The results are shown in Figures 1 and 2. Figure 1 is a graph showing the change in allulose content when allulose syrup with a pH of 5 and a 70% Brix concentration is stored at different temperatures. Figure 2 is a graph showing the change in allulose convertible product content when allulose syrup with a pH of 5 and a 70% Brix concentration is stored at different temperatures. As shown in Figures 1 and 2, the allulose content decreased and the allulose convertible product (Impurity-S) content increased as the storage temperature increased. Furthermore, to test the effect of pH on allulose and allulose converters, the 97.0% allulose-containing syrup from Example 1 was adjusted to different pH levels using caustic soda and hydrochloric acid solutions, stored at the same temperature (70°C), and sampled at different time intervals to analyze the changes in allulose content. The results are shown in Figures 3 and 4. Figure 3 is a graph showing the change in allulose content when allulose syrups with different pH levels and 70 Brix concentrations are stored at 70°C. Figure 4 shows the allulose conversion when allulose syrups with different pH levels and 70 Brix concentrations are stored at 70°C. This graph shows the change in content. As shown in Figures 3 and 4, at a temperature of 70°C, the lower the pH, the lower the allulose content and the higher the amount of allulose conversion product produced. Therefore, allulose is less stable at lower pH and higher temperatures, and its content changes during the actual production process, particularly during the concentration stage. This problem reduces the purity of high-purity allulose and significantly impacts the crystallization stage. In fact, during this process, the allulose content decreases and the content of a specific allulose converter (Impurity) that is additionally produced increases, and it has been confirmed that this component has a significant impact on allulose crystallization. It was found that when the content of a component called Impurity-S exceeds 2% among various allulose converters, it acts as a major inhibiting factor in the growth of allulose crystal particles, and this has been confirmed to have a significant impact on the particle size and crystal yield of the crystal particles.
[0100] Experimental Example 3: Characterization of Allulose Crystals (1) Analysis of the grain size distribution of crystals The particle size distribution of the allulose crystals obtained in Example 5 was confirmed using standard mesh sieves of different mesh sizes. Mesh sizes of 20, 30, 40, 60, 80, and 100 mesh were used for the standard mesh sieves, and the particle size distribution of the crystal grains was measured based on the size of the holes in the standard mesh sieves. The hole sizes of the standard sieves for each mesh size are 850, 600, 425, 250, 180, and 150 μm. 100 g of each sample was placed in the standard sieves corresponding to the mesh size and vibrated for 3 minutes to allow it to pass through. The weight of the sample remaining in the sieves for each mesh size was measured, and the percentage values are recorded in Table 5. In Table 5 below, the particle size distribution for each mesh size is shown numerically as a percentage of particle weight.
[0101] [Table 5]
[0102] As shown in Table 5 above, the allulose crystals of Example 5 showed a very narrow particle distribution concentrated at 90.2% by weight, while the allulose crystals of Example 3 showed the highest distribution at 40↑, but were evenly distributed at 80↑, 60↑, 40↑, and 30↑, confirming a broad particle distribution. It was confirmed that the smaller the ratio of long diameter to short diameter and the more rigid the crystalline particles, as in Example 5, the lower the fine powder content in the product and the more uniform the particle size distribution. Furthermore, the larger the ratio of long diameter to short diameter and the lower the uniformity of the particles, the more they become undifferentiated due to particle breakage during the drying and transport process, resulting in a non-uniform particle size distribution and a wide range of particle size distributions.
[0103] (2) Analysis of crystal morphology and crystal grain size Figure 5 shows an optical microscope image of the allulose crystal obtained in Example 5, measured at a magnification of X100. Figure 6 shows a scanning electron microscope (SEM) image of the allulose crystal obtained in Example 5, measured at a magnification of X100. Furthermore, the major diameter (vertical) and minor diameter (horizontal) were measured for the nine allulose crystal samples obtained in Example 5, and the particle diameter ratio (= major diameter / minor diameter) was obtained and is shown in Table 6 below. Specifically, the minor diameter length (μm) was set to 1 for five crystals, and the ratio of the major diameter length (μm) is shown based on this.
[0104] [Table 6]
[0105] As shown in Figure 6, the allulose crystal according to the present invention has a rectangular hexahedron or a crystal structure close to it. Taking the short diameter length (μm) of the crystal shown in Table 2 as 1, the ratio of the long diameter length (μm) to the short diameter length (μm) shown relative to this is, on average, 1.6 in the case of Example 5. Each crystal plane grows uniformly, forming an orthorhombic crystal morphology close to a square. Furthermore, it was confirmed that the longer diameter / short diameter ratio tends to decrease as the crystal planes grow more uniformly. This is interpreted as meaning that the lower the purity of the allulose raw material for crystallization, the more other components besides allulose act as impurities that hinder the crystal growth of pure allulose, thus affecting the crystal shape.
[0106] (3) Analysis using differential scanning calorimetry (DSC) DSC analysis was performed on the allulose crystals obtained in Example 5. The specific DSC analysis conditions were as follows: Equipment name: DSC [differential scanning calorimetry] Manufacturer: Perkin Elmer Method: Heating at 30-250°C, 10°C / min, N2 gas purging. (Reference method: ASTM D 3418) The DSC analysis results of the allulose crystals mentioned above are shown in Table 7 below.
[0107] [Table 7]
[0108] The DSC analysis results showed that the crystal in Example 5 had a high Tm value and a high heat capacity. DSC analysis of a crystal indicates that a higher heat capacity makes it less easily soluble, and a higher heat capacity and a narrower endothermic peak width predict that the crystal is uniformly and firmly formed. Considering the heat capacity and endothermic peak enthalpy value of Example 5, it was confirmed that the crystal in Example 5 was relatively more uniformly and firmly formed.
[0109] (4) Analysis of infrared absorption (IR) spectra To confirm the allulose crystals produced as described above, the infrared absorption (IR) spectrum of the crystals from Example 5 was analyzed under the following measurement conditions. Analytical instrument: TENSOR II with Platinum ATR, Manufacturer: Bruker (Germany) Detector: highly sensitive photovoltaic MCT detector with liquid nitrogen cooling Scan count: 64 scans at 20 kHz Scan range: 800-4,000 cm⁻¹ and averaged at 4cm-1 resolution. Analysis of the infrared absorption (IR) spectrum confirmed that the allulose molecular structure is composed of functional groups such as -OH, COC, CC, and C-OH, and possesses unique structural characteristics specific to the allulose molecule. Therefore, it was confirmed that the crystal in Example 5 is the same allulose crystal.
[0110] (5) Analysis by X-ray diffraction (XRD) X-ray diffraction analysis was performed on the allulose crystals obtained in Example 5 under specific analytical conditions. The top 5 peaks (Relative Intensity%) and morphologically specific peaks from the X-ray diffraction analysis of the allulose crystals obtained in Example 5 are selected and shown in Table 8. Analytical equipment: D / MAX-2200 Ultima / PC Manufacturer: Rigaku International Corporation (Japan) X-ray sauce system target: sealed tube Cu Tube voltage: 45kV / Tube current: 200mA Scan range: 5~80° 2θ Step size: 0.019° Scan speed: 5° / min
[0111] [Table 8]
[0112] As shown in Table 8 above, the allulose crystals obtained in Example 5 were found to have specific peaks on the powder X-ray spectroscopy spectrum at Angle 2-Theta degree values of 15.24, 18.78 and 30.84; 15.24, 18.78, 30.84 and 28.37; 15.24, 18.78, 30.84 and 31.87; 15.24, 18.78, 30.84 and 47.06; or 15.24, 18.78, 30.84, 28.37, 31.87 and 47.06.
Claims
1. Based on the total solids content, the allulose content is 90% by weight or more. The allulose conversion product (Impurity-S) content is 2% by weight or less. A composition for allulose crystallization having a solid content of 60 or more and 85 Brix (Bx) or less, The allulose crystals produced from the allulose crystallization composition are allulose crystals having the following characteristics (1) to (3): (1) A Tm temperature of 125.8°C ± 5°C is determined by differential scanning thermal analysis (DSC). (2) Differential scanning thermal analysis reveals a melting enthalpy (ΔH) of 200 to 220 J / g, (3) Having an average major diameter of 350 to 2,000 μm, The allulose conversion product (Impurity-S) is a substance whose mass / charge ratio, as measured by LC / MS analysis, falls within the range of 10 to 600 m / z. The allulose converter is Allulose dimer Allulose tetramer Levulinic acid (4-oxopentanoic acid), furfural Hydroxymethylfurfural (HMF), γ-Hydroxyvaleric acid (GVB), 2,5-Dimethylfuran 2,5-Furandic acid (FDCA), 5-hydroxymethyl-2-furonic acid 2,5-formylfurancarboxylic acid 2,5-Furandicarbaldehyde 2,5-bis-(hydroxymethyl)furan Bis(5-formyl-2-furfuryl) ether 2-Furonic acid 3-Furonic acid 5-Hydroxyfurfural 2,5-Dihydro-2,5-dimethoxyfuran (2R)-5-oxotetrahydro-2-furancarboxylic acid 5,5'-Methylenedi(2-furonic acid) (5,5'-Methylenedi(2-furonic acid)), and Bis(5-methylfurfuryl) ether A composition for allulose crystallization comprising one or more selected from the group consisting of the following.
2. The allulose crystallization composition according to claim 1, wherein the viscosity of the allulose crystallization composition is 2 cps to 200 cps at a temperature of 45°C.
3. The allulose crystallization composition according to claim 1, wherein the electrical conductivity of the allulose crystallization composition is 1,000 uS / cm or less.
4. The allulose crystallization composition according to claim 1, wherein the allulose conversion product is a substance having a maximum peak measured at an elution time of 31 minutes ± 2 minutes when analyzed by HPLC analysis.
5. The allulose crystallization composition according to claim 1, wherein the allulose converter (Impurity-S) comprises an allulose-modified polymer having a molecular weight 0.2 to 10 times that of allulose.
6. The allulose crystallization composition according to claim 1, wherein the pH of the composition is 4 to 7.
7. The allulose crystallization composition according to claim 1, wherein the temperature of the composition is adjusted to 70°C or lower.
Citation Information
Patent Citations
Method for producing d-psicose crystal
JP2011206054A
Method for producing d-psicose crystals
JP2017532382A
Mixed sugar granular powder and method for preparing same
WO2016182235A1